1998
DOI: 10.1074/jbc.273.26.16576
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Secreted β-Amyloid Precursor Protein and Amyloid β-Peptide in Brain by Cholesterol

Abstract: The effects of dietary cholesterol on brain amyloid precursor protein (APP) processing were examined using an APP gene-targeted mouse, genetically humanized in the amyloid ␤-peptide (A␤) domain and expressing the Swedish familial Alzheimer's disease mutations. These mice express endogenous levels of APP holoprotein and abundant human A␤. Increased dietary cholesterol led to significant reductions in brain levels of secreted APP derivatives, including sAPP␣, sAPP␤, A␤1-40, and A␤1-42, while having little to no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
125
2
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(136 citation statements)
references
References 87 publications
(76 reference statements)
5
125
2
4
Order By: Relevance
“…76 Thus RAGE plays a direct and indirect role in AD pathogenesis, in particular, the apparent inverse relationship between sRAGE and cholesterol may add yet another modulatory effect on Ab metabolism as cholesterol is a known mediator of inflammation and APP processing. [93][94][95][96][97][98][99][100][101][102][103][104] Efflux of Ab: LRP-1/Ab interactions at BBB LRP-1 is a multi-ligand lipoprotein receptor involved in the mediation of endocytosis or activation of signalling molecules for a diverse range of secreted and membrane-bound ligands. Receptor activating protein (RAP) is a 39 kDa chaperone protein that binds to LRP-1 and regulates its tertiary structure.…”
Section: Influx Of Ab Rage/ab Interactions At Bbbmentioning
confidence: 99%
“…76 Thus RAGE plays a direct and indirect role in AD pathogenesis, in particular, the apparent inverse relationship between sRAGE and cholesterol may add yet another modulatory effect on Ab metabolism as cholesterol is a known mediator of inflammation and APP processing. [93][94][95][96][97][98][99][100][101][102][103][104] Efflux of Ab: LRP-1/Ab interactions at BBB LRP-1 is a multi-ligand lipoprotein receptor involved in the mediation of endocytosis or activation of signalling molecules for a diverse range of secreted and membrane-bound ligands. Receptor activating protein (RAP) is a 39 kDa chaperone protein that binds to LRP-1 and regulates its tertiary structure.…”
Section: Influx Of Ab Rage/ab Interactions At Bbbmentioning
confidence: 99%
“…In transgenic mice expressing the Swedish familial AD mutations, changes in concentrations of sAPP and Ab in brain were all negatively correlated with serum cholesterol concentrations. 47 ABCA1 promotes cholesterol efflux from cells and is required for maintaining plasma cholesterol concentrations. In a study by Burns et al 18 overexpression of ABCA1 achieved by stimulating liver X receptors increased plasma cholesterol and apo E, commensurate with a decrease in brain Ab.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies using immortalized and primary cell lines [83][84][85] have demonstrated that increased cholesterol levels can increase the activity of the ␤-secretase pathway, leading to an accumulation of A␤ and A␤ 1-42 peptides, with a resulting increase in formation of extracellular amyloid deposits. Moreover, it has recently been demonstrated that cholesterol is capable of modulating the production of mature glycosylated APP.…”
Section: Cholesterol Homeostasis In Neurodegenerative Conditionsmentioning
confidence: 99%